Black Jeremiads: Maria W. Miller Stewart’s Jeremiah Appropriation for Liberation - Chan, Xenia Ling-Yee (Black theology, 2025)
Maria W. Miller Stewart, an African American abolitionist, moral reformer, and educator, has been called America's preeminent Black Woman Jeremiah. Attracting large crowds with her abolitionist speeches in the 1830s, her writings, sermons, and lectures were thick with knowledge of the scriptures, with her original thoughts and scriptural references nearly indistinguishable in her personification of a biblical prophet to her context. The question explored is to what degree Stewart's reception and appropriation of the book of Jeremiah influenced her effect as a Jeremiah in her own time. I argue Stewart demonstrated how the act of textual appropriation is central to the embodiment, experience, and liberation of her community and nation. Further, Stewart's textual appropriation – leading her to air numerous social and political grievances within and external to the African American community – laid the foundation for her rhetoric, providing agency for resistance for the African American community and other abolitionists.